The Correlation Between Teaching Readiness and The Implementation of 21st Century Learning Among Trainee Teachers in Sultan Idris Education University - Mohammad, Syafiq Idham; Nallaluthan, Kesavan; Subramanium, Premila; Zainal, Mazlan; Kolandan, Subramaniam; Balamurugan; Balasundram, Nilavathi (Jurnal Pendidikan Bitara UPSI, 2024)
This study was conducted to identify the level of teaching readiness in terms of knowledge and information and communications technology skills (ICT), as well as the level of implementation of 21st century learning. The study also assessed the relations between knowledge and ICT skills and examined the relations between teaching readiness and the implementation of 21st century learning among trainee teachers in Sultan Idris Education University (UPSI). A quantitative approach was employed using a survey method, involving a sample of 351 trainee teachers who had undergone their first teaching practice. The study sample was selected using a proportional stratified random sampling technique. Data collection was done through a questionnaire to assess the teaching readiness of trainee teachers in applying 21st century learning. The study data were analyzed using the Statistical Package for Social Science (SPSS) version 29, involving both descriptive and inferential statistics analysis. Pearson correlation tests were used to examine significant relationships between the variables. The findings of the study revealed that the teaching readiness level was high, and the implementation of 21st century learning was also high, with mean scores of 4.29 (SD = 0.369) and 4.01 (SD = 0.271) respectively. The results also indicated a significant positive relationship between the two sub-constructs and between teaching readiness and implementation of 21st century learning. In summary, the findings of this study demonstrate the significance of implementing 21st century teaching and learning practices and ICT skills in enhancing the efficiency and effectiveness of the educational process at the school level. These practices serve as the foundation for developing more innovative and impactful educational strategies in the future1.